IMPLEMENTASI PENDIDIKAN KARAKTER RELIGIUS MELALUI BUDAYA SEKOLAH DI SD MUHAMMADIYAH WIROBRAJAN 1 YOGYAKARTA - M. Ilham Darmawan; Azamul Fadhly Noor Muhammad (STKIP Subang, 2026)
This study aims to determine the process of implementing religious character education through school culture at SD Muhammadiyah Wirobrajan 1 Yogyakarta, namely the planning process, implementation, supporting factors, inhibiting factors, results, and evaluation. The background of this study is based on the application of character education through school culture, which has a positive impact on the character building of students primary schools. This study was a qualitative study using a descriptive approach. The population consisted of the principal, teachers, and students. Data collection techniques included interviews, observation, and documentation. The data obtained were analyzed through data collection, data reduction, data presentation, and conclusions. Data validity was checked using triangulation. The results of the study show that the implementation of religious character education through school culture at SD Muhammadiyah Wirobrajan 1 Yogyakarta has been carried out through three cultures, namely academic, socio-cultural, and democratic, which contains the values of worship, morals, behaviour and human values. The guidelines used are the vision, mission, school objectives, the Ministry of National Education, and Muhammadiyah. Planning is used for the preparation programmes, documents, curriculum, lesson plans, and evaluations. Implementation was carried out through learning, school programmes, and habits. Supporting factors are vision, mission, objectives, programmes, facilities, infrastructure, school environment, teachers, and parents. Obstacles came from internal factors of students, teachers, and the environment outside school. The results of implementing religious character education through school culture have generally been quite good, in line with the objectives. Evaluation is carried out through direct and routine observation techniques.